Нormonal status of aged rats with diet-induced obesity after umbilical cord blood administration - Bondarenko, Е.А.; Babiychuk, V. G.; Babiychuk, L. V. (CRYO 2022: the 59th joint meeting of the Society for Cryobiology and Society for Low Temperature Biology - A hybrid event. Dublin, Ireland, 19 – 22.07. 2022., 2022)
The number of obese people steadily increases. Disorders of central mechanisms of regulation, when the eating behavior changes and body’s neurohormonal shifts occur, are observed in obesity. The objective herein was to evaluate the impact of administration of cryopreservednucleated cord blood cells (cNCBCs) on hormonal status of aged rats with obesity. Experiments were approved by the Bioethics Committee of the Institute for Problems of Cryobiology and Cryomedicine of the NAS of Ukraine. Thawed CBNCs preparation was injected intraperitoneally in dose of 3×105 CD34+- cells/kg. The preparation was made up to 1 ml volume with plasma autologous to the cells. The next day, a week and a month after cord blood injection the animals were sacrificed and blood was sampled for further studies. The content of thyroxine (T4), triiodothyronine (T3), testosterone (Ts), estradiol (ES) and dehydroepiandrosterone sulfate (DHEAS) was determined by enzyme-linked immunosorbent assay using the standard ELISA kits. The obesity was accompanied by a significant decrease in thyroid and sex hormone concentration in blood serum of aged rats. The cNCBCs administration the next day, a week and a month later promoted increasing not only the total T3 level, but also total T4 one in blood serum of aged obese rats, accompanied by a significant increase in Ts concentration as well. The cNCBCs injection augmented the functional activity of thyroid and sex glands, normalized the Ts level, thus increasing the adaptive and compensatory body potential in aged obese animals. The revealed changes are physiologically significant, since thyroid hormones increase the oxygen absorption by organs and tissues, regulate the metabolism of lipids and carbohydrates, thereby participating in energy metabolism and maintaining the constancy of body weight. If a metabolic rate increases, the proteins and fats are decomposed under thyroid hormone impact, resulting in decreased appetite and body weight loss.
Bondarenko E. А., Babiychuk V. G., Babiychuk L. V. Нormonal status of aged rats with diet-induced obesity after umbilical cord blood administration. CRYO 2022: the 59th joint meeting of the Society for Cryobiology and Society for Low Temperature Biology - A hybrid event. Dublin, Ireland, 19 – 22.07. 2022. Р. 170–171.
Keywords: diet-induced obesity; umbilical cord blood; hormonal status; rats